The Effect of Hotel Tax, Restaurant Tax, Eentertaiment Tax and The Number of Tourists on Locally-Generated Revenue at Bintan Districts - Hadli Lidya Rikayana; Nurhasanah (Journal of Business, Management, & Accounting, 2020)
The purpose of this study was to examine the effect of hotel taxes, restaurant taxes, entertainment taxes, and the number of tourists on local revenue in Bintan Regency in 2015-2018. This type of research is descriptive, the type of data obtained is secondary data in the form of time series data with data collection techniques in the form of observation and literature study techniques. The data analysis method used in this research is the classical assumption test and hypothesis testing. The results of this study indicate that (1) hotel taxes have an effect on local revenue because tcount 2,240> ttable 2,01669 and a significance value of 0.030> 0.05. (2) restaurant tax has no effect on local revenue because tcount 0.090 <ttable 2.01669 and a significance value of 0.929 <0.05. (3) entertainment tax has no effect on local revenue because tcount 1-1.833 <ttable 2.01669 and a significance value of 0.074> 0.05. (4) the number of tourists has an effect on local revenue because tcount 2.043 <ttable 2.01669 and a significance value of 0.047> 0.05. (5) hotel tax, restaurant tax, and entertainment tax have a simultaneous effect on local revenue because Fcount is 6.074> Ftable 2.82 and a significance value of 0.001 <0.05.